Efficacy and safety of ustekinumab in psoriatic arthritis patients with peripheral arthritis and physician-reported spondylitis: post-hoc analyses from two phase III, multicentre, double-blind, placebo-controlled studies (PSUMMIT-1/PSUMMIT-2). Issue 11 (20th April 2016) - Kavanaugh, Arthur; Puig, Lluis; Gottlieb, Alice B; Ritchlin, Christopher; You, Yin; Li, Shu; Song, Michael; Randazzo, Bruce; Rahman, Proton; McInnes, Iain B
Abstract : Objective: To evaluate ustekinumab efficacy and safety in psoriatic arthritis (PsA) patients with peripheral arthritis and physician-reported spondylitis (termed the 'spondylitis subset'). Methods: Adults with active PsA (PSUMMIT-1/PSUMMIT-2, n=615/312) were randomised to ustekinumab 45 mg, 90 mg or placebo at week 0/week 4/q12 week. At week 16, patients with <5% improvement in tender and swollen joints entered blinded early escape. A subset of patients with physician-identified spondylitis was evaluated with spondylitis-specific assessments, including Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Ankylosing Spondylitis Disease Activity Score employing C reactive protein (ASDAS-CRP), through week 24. Results: 256/927 (27.6%) PSUMMIT-1/PSUMMIT-2 patients (placebo/ustekinumab, n=92/164) comprised the evaluable spondylitis subset. At week 24, in this analysis subset, significantly more patients achieved BASDAI20/50/70 responses (54.8%/29.3%/15.3% vs 32.9%/11.4%/0%; p≤0.002), improvement in BASDAI question 2 concerning axial pain (1.85 vs 0.24; p<0.001) and mean per cent ASDAS-CRP improvements (27.8% vs 3.9%; p<0.001) for ustekinumab versus placebo recipients, respectively. Comparable to the overall study population, significant improvements were also achieved in psoriasis, peripheral arthritis, enthesitis, dactylitis, physical function and peripheral joint radiographs in the spondylitis subset. Conclusions: In this post-hoc analysis of PsA patients with baseline peripheral arthritis and physician-reported spondylitis, ustekinumab-treated patients demonstrated significant improvements in axial signs and symptoms through week 24. Trial registration number: PSUMMIT-1 (NCT01009086, EudraCT 2009-012264-14) and PSUMMIT-2 (NCT01077362, EudraCT 2009-012265-60); post-study results.